A Two-Years' Survey on the Prevalence of Tuberculosis Caused by Mycobacterium caprae in Red Deer (Cervus elaphus) in the Tyrol, Austria. (22nd October 2012) - Schoepf, Karl; Prodinger, Wolfgang M.; Glawischnig, Walter; Hofer, Erwin; Revilla-Fernandez, Sandra; Hofrichter, Johannes; Fritz, Johannes; Köfer, Josef; Schmoll, Friedrich
Abstract : A survey of 143 hunter-harvested red deer for tuberculosis was conducted in an Alpine area in Western Austria over two subsequent years. There, single tuberculosis cases caused by Mycobacterium caprae had been detected in cattle and red deer over the preceding decade. The area under investigation covered approximately 500 km 2, divided into five different hunting plots. Lymph nodes of red deer were examined grossly and microscopically for typical tuberculosis-like lesions and additionally by microbiological culturing. Executing a detailed hunting plan, nine M. caprae isolates were obtained. Six out of nine originated from one single hunting plot with the highest estimated prevalence of tuberculosis, that is, 23.1%. All isolates were genotyped by mycobacterial interspersed repetitive unit—variable number of tandem repeat (MIRU-VNTR) typing of 24 standard loci plus VNTR 1982. All nine isolates belonged to a single cluster termed "Lechtal" which had been found in cattle and red deer in the region, demonstrating a remarkable dominance and stability over ten years. This is the first report on a systematic prospective study investigating the prevalence and strain variability of M. caprae infection in red deer in Austria and in the Alpine countries.